2006
DOI: 10.1021/ma061139i
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl End-Functionalized Oligoesters:  Correlation between Wettability and End-Group Segregation

Abstract: We report a detailed investigation of the processes of the surface segregation in correlation with the wetting properties of perfluoroalkyl end-functionalized linear aromatic oligoesters. We have compared properties of films containing different fluorine concentration prepared by the spin-coating technique and by melting of polymer grain onto the supported substrate. We demonstrate that both methods can be used for the preparation of highly hydrophobic and oleophobic surfaces. Obtained layers possess high valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
64
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 36 publications
8
64
0
Order By: Relevance
“…Again, the surface roughness seems to be responsible for the large increase in CA (compare TZF with TZ 4 /TZF and TZS 4 /TZF in Table 4) and the CAs of the multilayer samples with the last fluorinated top layer are much higher than those on multilayer sample with only inorganic layers (compare TZS 5 and TZS 4 /TZF in Table 4). The CA of n-hexadecane on the fluorinated monolayer TZF was found to be in reasonable agreement (θ adv /θ rec = 88 • /85 • ) to our previously reported data for fluorinated polyesters [43]. Increase in the number of inorganic layers coated by fluorinated material leads to an increase in nhexadecane CA (compare data for TZS 1 /TZF and TZS 4 /TZF coatings in Table 3).…”
Section: Discussionsupporting
confidence: 87%
“…Again, the surface roughness seems to be responsible for the large increase in CA (compare TZF with TZ 4 /TZF and TZS 4 /TZF in Table 4) and the CAs of the multilayer samples with the last fluorinated top layer are much higher than those on multilayer sample with only inorganic layers (compare TZS 5 and TZS 4 /TZF in Table 4). The CA of n-hexadecane on the fluorinated monolayer TZF was found to be in reasonable agreement (θ adv /θ rec = 88 • /85 • ) to our previously reported data for fluorinated polyesters [43]. Increase in the number of inorganic layers coated by fluorinated material leads to an increase in nhexadecane CA (compare data for TZS 1 /TZF and TZS 4 /TZF coatings in Table 3).…”
Section: Discussionsupporting
confidence: 87%
“…In general, perfluorinated species of fluoropolymers tend to segregate onto the outer surface due to their low surface energies [29,30]. Therefore, fluoropolymers have often been studied as surface-modifying additives of polymer blends, in order to control their surface properties [31].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the chain shapes or the conformations of polymers in solutions could affect the structures and properties of the polymers in bulk [22,23]. The influence of the preparation methods on the surface properties of fluorinated polymers has been reported in several publications [21,[24][25][26][27][28][29] and it was found that various surface structures can be obtained by controlling film-formation conditions such as the solvent species and preparation methods. When methyl methacrylate (MMA) and 2-perfluorooctylethyl methacrylate (FMA) block copolymer (PMMA-b-PFMA) film was prepared from its micelle solution with PMMA block as micelle corona and PFMA block as 0021-9797/$ -see front matter Ó 2010 Elsevier Inc. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…When methyl methacrylate (MMA) and 2-perfluorooctylethyl methacrylate (FMA) block copolymer (PMMA-b-PFMA) film was prepared from its micelle solution with PMMA block as micelle corona and PFMA block as 0021-9797/$ -see front matter Ó 2010 Elsevier Inc. All rights reserved. doi:10.1016/j.jcis.2010.05.042 micelle core, the segregation of fluorinated moieties was affected greatly by micelle stability and the solvent's evaporation rate [26][27][28]30]. The rapid solvent evaporation rate plus the good micelle stability resulted in forming a micelle-like aggregate structure at the film surface, on which the PMMA coronas are partly exposed to the surface [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation